Application of small-diameter round timber as structural members in light frame construction. Issue 3 (4th May 2022) - Wu, Guofang; Zhu, Enchun; Ren, Haiqing; Zhong, Yong; Gong, Meng
ABSTRACT: Small-diameter round timber is a kind of by-product mainly from the thinning operation of the plantations. It is plentiful and inexpensive, and is generally destined for non-structural applications. The small-diameter round timber is rarely used as structural members. This study was aimed to provide an innovative but simple way to use the small-diameter round timber as structural members. Three kinds of composite members were developed to be used in light frame wood construction, i.e. the built-up studs, the wood-steel joists and the wood-steel roof trusses. The shearwalls and diaphragms made of the developed composite members were also examined. To facilitate the fabrication, the configurations of these members were described in details. Efforts were also made to investigate the structural performances of these members via full-scale tests. It was found that the developed composite members could be used as substitutes of dimension lumber in the framework of light frame construction. The developed members could be also pre-fabricated as standard components in a mill and assembled on site. As a result, application of small-diameter round timber as structural members developed would be an efficient way to increase use of forest resource from plantation and lower the construction cost of light frame buildings.